The deepest sense : a cultural history of touch - Classen, Constance, 1957- (Studies in sensory history., 2012)
From the softest caress to the harshest blow, touch lies at the heart of our experience of the world. Now, for the first time, this deepest of senses is the subject of an extensive historical exploration. The Deepest Sense: A Cultural History of Touch fleshes out our understanding of the past with explorations of lived experiences of embodiment from the Middle Ages to modernity. This intimate and sensuous approach to history makes it possible to foreground the tactile foundations of Western culture--the ways in which feelings shaped society. Constance Classen explores a variety of tactile realms including the feel of the medieval city; the tactile appeal of relics; the social histories of pain, pleasure, and affection; the bonds of touch between humans and animals; the strenuous excitement of sports such as wrestling and jousting; and the sensuous attractions of consumer culture. She delves into a range of vital issues, from the uses--and prohibitions--of touch in social interaction to the disciplining of the body by the modern state, from the changing feel of the urban landscape to the technologization of touch in modernity. Through poignant descriptions of the healing power of a medieval king's hand or the grueling conditions of a nineteenth-century prison, we find that history, far from being a dry and lifeless subject, touches us to the quick."--Publisher's website